Biogeochemical Reconstruction of Authigenic Carbonate Deposits at Methane Seep Site off Krishna‐Godavari (K‐G) Basin, Bay of Bengal - S. P. K. Pillutla; A. Peketi; A. Mazumdar; Mohd. Sadique; K. Sivan; Anjali Zatale; S. Mishra; Swati Verma (Geochemistry, Geophysics, Geosystems, 2024)
Abstract Active and relic marine methane‐seep sites are widely distributed globally and are distinguished by distinctive geology, biogeochemistry, and ecosystems. The discovery of methane‐seep sites in the Krishna‐Godavari (K‐G) basin has created exciting new opportunities for methane‐seep research in the Bay of Bengal. In this study, we document the occurrence of authigenic carbonates, including micro‐crystalline aragonite crust (arg‐crusts) admixed with chemosynthetic shells and high‐magnesium carbonate tubular structures (HMC‐tube), from the methane‐seep site SSD‐045/4 in the K‐G basin. The δ13C values of HMC‐tubes (−54.5 to −46.2‰) and arg‐crusts (−57.6 to −34.8‰) indicate biogenic methane as the likely carbon source. Enhanced porewater alkalinity driving carbonate precipitation may be attributed to microbial‐mediated SO₄2−‐AOM processes. Additionally, δ13C values (−35.2 ± 8‰) of the residual organic matter within the carbonates suggest a contribution of methanotrophic bacterial biomass. The δ18Ocarb values of HMC and aragonite indicate methane hydrate degassing and crystallization pathways, respectively. Pelloid‐filled burrows suggest the reworking of shallow HMC deposit by burrowing organisms, whereas the polyphase cementations (aragonite and HMC) within burrows indicate early and burial diagenetic pathways. The wide range in ΣLREE/ΣHREE ratios and Ceanom values in arg‐crusts reflect micro‐spatial variations in redox conditions, likely due to cementation occurring in both open and closed diagenetic systems. In contrast, more constrained Ceanom values and ΣLREE/ΣHREE ratios in HMC tubes suggest persistent sulfidic conditions. Overall, these findings provide insights into the pathways of carbonate formation at the K‐G basin methane‐seep site, highlighting the complex interplay of microbial processes, fluid dynamics, and diagenetic alterations.